Maxwellian evolution equations along the uniform optical fiber - Korpinar, Talat; Demirkol, Ridvan Cem; Korpinar, Zeliha; Asil, Vedat (Elsevier Gmbh, 2020)
[Abstract Not Available]
Keywords: Berry Topological Phase; Polarization; Rotation